THU0231 IL-17 polarization of mait cells derive from the activation of two different pathways. (15th June 2017) - Guggino, G; Ciccia, F; Pizzo, M Lo; Liberto, D Di; Saieva, L; Ruscitti, P; Cipriani, P; Sireci, G; Alessandro, R; Dieli, F; Giacomelli, R; Triolo, G
Abstract : Background: Primary Sjogren Syndrome (pSS) is a chronic inflammatory disorder affecting exocrine glands. Both IL-23 and the downstream cytokines IL-17 and IL-22 are recognised as key players in the disease. Therefore, the identification of the cellular sources and inducers of IL-17 is crucial in the understanding of the drivers of inflammation in pSS. Mucosal-associated invariant T (MAIT) cells recognize riboflavin derivatives presented by the MHC class I-like molecule MR1. Objectives: Recently, MAIT cells have been implicated in the pathogenesis of autoimmune disorders and found expanded in salivary glands of pSS patients. Their expression of IL7R and IL23R, makes them potential contributors to the pathogenesis of pSS. Methods: Mononuclear cells from 16 patients with pSS and 14 subjects with non Sjogren Syndrome secca syndrome (nSS) were isolated from blood and salivary glands. We assessed the phenotype and cytokine expression of MAIT cells by surface and intracellular flow cytometry analysis. The function of MAIT cells was assessed upon in vitro stimulation with recombinant IL-7, IL-23 or their specific ligand lumazine (a Vitamin B2 precursor previously reported to be recognized by and specifically activate MAIT cells). Results: MAIT cells were reduced in frequency in peripheral blood but not in minor salivary glands of patients with pSS, compared with nSS. In vitro stimulation of MAIT cells from pSS patients induced cytokine production which was dependent on priming with IL-7, IL-23 or specific antigen (lumazine) stimulation. Particularly, IL-7 and IL-23 guarantee IL-17 polarization of MAIT cells by two different pathways via the activation of STAT3 or RORc respectively. Conclusions: This study confirms a potential role for MAIT cells in pSS and, for the first time, links IL-7 and IL-23 to the IL-17 polarization of MAIT cells in these patients. Disclosure of Interest: None declared